Ask a New Question
Search
(-1+i)(-1-i) in polar form
1 answer
-1+i = (√2,3π/4)
-1-i = (√2,5π/4)
so,
(-1+i)(-1-i) = (√2*√2,3π/4 + 5π/4) = (2,2π) or (2,0)
You can see this since
(-1+i)(-1-i) = (-1)^2 - i^2 = 1+1 = 2
Ask a New Question
or
answer this question
.
Similar Questions
1)What is the correct structure of AsH3???? 2)Name the type of hybrid orbitals of central form. 3) Name the molecular geometry
10 answers
Convert the rectangular coordinate (2,-2) to polar form and find two additional representations of this point.
Can you check my
1 answer
convert from polar form into rectangular form. type the equation in rectangular form (simplified):
1) rsecθ = 3 2)
2 answers
Determine the two square roots of 3+j4 in both a)Cartesian form
b) Polar form Any help with this question would appreciated
1 answer
more similar questions